(REHABILITATING HERITAGE PLACES) STRUCTURAL REPAIRS AND CONSERVATION WORKS FOR ASTOR KOLKATA, INDIA - S. Dasgupta; L. Fournier (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2017)
Kolkata, formerly known as Calcutta in English, is the capital of the Indian state of West Bengal and is located in eastern India on the east bank of the River Hooghly. The city was a colonial city developed by the British East India Company and then by the British Empire. Kolkata was the capital of the British Indian empire until 1911 when the capital was relocated to Delhi. Kolkata grew rapidly in the 19th century to become the second city of the British Empire. This was accompanied by the development of a culture that fused European philosophies with Indian tradition. The city has been known by many names "Cultural Capital of India", "The City of Processions", "The City of Palaces", and the "City of Joy". Problems related to rapid urbanisation started to plaque Kolkata from the 1930s and the city remains an example of the urbanization challenges of the developing nations. The exercise included Archival research, Field surveys, Condition Mapping, structural evaluation and preparation of restoration & conservation solutions along with post conservation management plan. The Major challenges encountered were identifying the correct consolidation techniques using modern technology and incorporation of modern services. The Documentation and Mapping was used as a significant tool to guide towards the structural consolidation, conservation and Management strategy of the complex.